Integration of Targhib -Tarhib and Neurospiritual Education: Innovation in Transcendental-Affection-Based Islamic Character Education in the Generation Z Era - Rully Nasrulloh; Nida Syahida Nahdlotusilmi (Islamic Journal of Education, 2025)
This article discusses the integration of the Targhib-tarhib method with the neurospiritual education approach in Islamic character education, particularly among Generation Z. Amidst technological developments and changing social values, this generation faces serious challenges in forming a strong and sustainable Islamic character. Targhib (reward motivation) and tarhib (punishment warning) are classical Islamic methods that have proven effective in moral formation, but their application today requires renewal in line with the psychological and neurological context of students. With a neurospiritual approach, this method not only touches on the cognitive dimension but also influences the limbic system, hormonal system, and spiritual affection center (such as fear, hope, and love for Allah). Literature studies and thematic analyses of several journals and educational experiment results show that this integration can enhance the effectiveness of Islamic character building in a more profound way, touching the affective-transcendental side of students. This research recommends the development of a neurospiritual-based Islamic character curriculum that is adaptive to the needs and challenges of Generation Z.